Answer:
Step-by-step explanation: First we substitute x as 3
then,the equation will be 4×3+3×y=36(we should no that there is a hidden multiplication sign between 4 and x (3) and 3 and y)
- also between 4x and 3y there is a hidden multiplication sign
then we can simplify the equations as 12+3y=36
if we want to make the unknown number that is 3y independent we must remove 12.How do we do it? we know that + and - gives neutral so
12-12+3y=36-12(now we have put 12 to the other side making the unknown value independent.Also infront of 12 there is an invisible + sign)
now we can simplify it further +12-12=0
3y=36-12
3y=24
now to find y we have to remove 3 from it .we know its 3×y, right
so if we do the opposite sign 3 will get removed
then 3y ÷3=24÷3 (why i divided 24 also by 3 is , if i add a mathematical equation to one term of the equation i have to do it for others too)
then the equations will be y=8
and the answer is D